Altered Ca2+ and Na+ Homeostasis in Human Hypertrophic Cardiomyopathy: Implications for Arrhythmogenesis - Coppini, Raffaele; Ferrantini, Cecilia; Mugelli, Alessandro; Poggesi, Corrado; Cerbai, Elisabetta (Frontiers in Physiology, 2018)
Hypertrophic cardiomyopathy (HCM) is the most common mendelian heart disease, with a prevalence of 1/500. HCM is a primary cause of sudden death, due to an heightened risk of ventricular tachyarrhythmias that often occur in young asymptomatic patients. HCM can slowly progress toward heart failure, either with preserved or reduced ejection fraction, due to worsening of diastolic function. Accumulation of intra-myocardial fibrosis and replacement scars underlies heart failure progression and represents a substrate for sustained arrhythmias in end-stage patients. However, arrhythmias and mechanical abnormalities may occur in hearts with little or no fibrosis, prompting toward functional pathomechanisms. By studying viable cardiomyocytes and trabeculae isolated from inter-ventricular septum samples of non-failing HCM patients with symptomatic obstruction who underwent myectomy operations, we identified that specific abnormalities of intracellular Ca2+ handling are associated with increased cellular arrhytmogenesis and diastolic dysfunction. In HCM cardiomyocytes, diastolic Ca2+ concentration is increased both in the cytosol and in the sarcoplasmic reticulum and the rate of Ca2+ transient decay is slower, while the amplitude of Ca2+-release is preserved. Ca2+ overload is the consequence of an increased Ca2+ entry via L-type Ca2+-current [due to prolongation the action potential (AP) plateau], combined with a reduced rate of Ca2+-extrusion through the Na+/Ca2+ exchanger [due to increased cytosolic (Na+)] and a lower expression of SERCA. Increased late Na+ current (INaL) plays a major role, as it causes both AP prolongation and Na+ overload. Intracellular Ca2+ overload determines an higher frequency of Ca2+ waves leading to delayed-afterdepolarizations (DADs) and premature contractions, but is also linked with the increased diastolic tension and slower relaxation of HCM myocardium. Sustained increase of intracellular [Ca2+] goes hand-in-hand with the increased activation of Ca2+/calmodulin-dependent protein-kinase-II (CaMKII) and augmented phosphorylation of its targets, including Ca2+ handling proteins. In transgenic HCM mouse models, we found that Ca2+ overload, CaMKII and increased INaL drive myocardial remodeling since the earliest stages of disease and underlie the development of hypertrophy, diastolic dysfunction and the arrhythmogenic substrate. In conclusion, diastolic dysfunction and arrhythmogenesis in human HCM myocardium are driven by functional alterations at cellular and molecular level that may be targets of innovative therapies.